The Effectiveness of Using Narrative Text in Teaching Writing Narrative Text ( A Pre Experimental Study At Class X Of Ma Al- Munawaroh in the Academic Year 2021-2022) - Asriyani, Susila Dhihayu (JELLE, 2023)
Abstract: The researcher conducted research at MA Al-Munawaroh at tenth grade. This study aims to determine the achievements of students before and after being taught using animation film and to find out whether there is a significant difference between students' achievements in writing narrative text before and after being taught using animation film. This research is a pre-experimental quantitative research design that uses only 1 class to examine. The sample in this study is class X-B which collects 20 students. The sample used is purposive sampling technique. The instrument used is a written test. And for data collection with pretest and posttest which were analyzed using normality test, paired sample t-test with SPSS version 25. The results showed that there was a significant difference between the results of the pretest and posttest. The average score for the post-test was (75.5) above the Minimum Completeness Criteria (KKM) of seventy (70), while the average score for the pretest was below the Minimum Completeness Criteria (KKM). ) seventy (70), the score is (57.85), which means the post-test score is higher than the pre-test score. Based on the paired sample test, the results of a comparative analysis using the T-test it is known that sig. (2-tailed) 0.000, while alpha (α) 0.05 (0.000 <0.05) means that Ho is rejected and Ha is accepted. In other words, the use of animation film media in teaching writing narrative text is effective.Keywords: Animation Film, Writing, Narrative Text